Associations between nutritional factors and chemotherapy toxicity in older adults with solid tumors. Issue 8 (24th January 2020) - Dotan, Efrat; Tew, William P.; Mohile, Supriya G.; Ma, Huiyan; Kim, Heeyoung; Sun, Can‐Lan; Caan, Bette; Dale, William; Gajra, Ajeet; Klepin, Heidi D.; Owusu, Cynthia; Gross, Cary P.; et al.
Abstract : Background: Nutritional status can directly affect morbidity and mortality in older adults with cancer. This study evaluated the association between pretreatment body mass index (BMI), albumin level, and unintentional weight loss (UWL) in the prior 6 months and chemotherapy toxicity among older adults with solid tumors. Methods: This was a secondary analysis of a prospective, multicenter study involving chemotherapy‐treated patients 65 years old or older. Geriatric assessment, BMI, albumin level, and UWL data were collected before treatment. Multivariable logistic regression models evaluated the associations between nutritional factors and the risk of grade 3 or higher (grade 3+) chemotherapy toxicity. Results: Seven hundred fifty patients with a median age of 72 years (range, 65‐94 years) and mostly stage IV disease were enrolled. The median pretreatment BMI and albumin values were 26 kg/m 2 (range, 15.1‐52.1 kg/m 2 ) and 3.9 mg/dL (range, 1.0‐5.0 mg/dL), respectively. Nearly 50% of the patients reported UWL, with 17.6% reporting >10% UWL. Multivariable analysis revealed no association between >10% UWL and a risk for grade 3+ chemotherapy toxicity (adjusted odds ratio [AOR], 0.87; P  = .58). Multivariable analysis showed a trend toward an association between a BMI ≥ 30 kg/m 2 and a decreased risk of grade 3+ chemotherapy toxicity (AOR, 0.65; P  = .06), whereas a low albumin level (≤3.6 mg/dL) was associated with a higher risk of grade 3+ chemotherapy toxicity (AOR, 1.50; P  = .03). An analysis of the joint effect of BMI and albumin demonstrated the lowest risk of grade 3+ chemotherapy toxicity among patients with high BMIs (≥30 kg/m 2 ) and normal albumin levels (AOR, 0.41; P  = .008). Conclusions: Among older adults with solid tumors, higher BMIs and normal albumin levels are associated with a lower risk of grade 3+ chemotherapy toxicity. Additional research is warranted to define the clinical significance of nutritional markers and to inform future interventions. Abstract : This study evaluates the association between nutritional factors and the risk of chemotherapy toxicity among older adults with solid tumors. Body mass index and albumin are identified as the strongest predictors for chemotherapy tolerance in this patient population.